2006
DOI: 10.1677/joe.1.06728
|View full text |Cite
|
Sign up to set email alerts
|

Pup removal suppresses estrogen-induced surges of LH secretion and activation of GnRH neurons in lactating rats

Abstract: During lactation, the suckling stimulus exerts profound influences on neuroendocrine regulation in nursing rats. We examined the acute effect of pup removal on the estrogeninduced surge of LH secretion in ovariectomized lactating rats. Lactating and nonlactating cyclic female rats were given an estradiol-containing capsule after ovariectomy, and blood samples were collected through an indwelling catheter for serum LH determinations. In lactating, freely suckled ovariectomized rats, estrogen treatment induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…First, in five of them (mPOAd, mPOAv, LHb, SUM, VMH), and even in some sites that did not have significant main effects of or interactions with litter presence (e.g., CG, BSTd, MS, LSvl, PVNp, NAc, LH), a comparison of the unstimulated controls reveals that simply removing the litter produced a 2-6-fold increase in Fos expression. This is not the result of a physiological stress response, because temporary removal of the litter actually decreases maternal glucocorticoid levels, not increases them [24,78,90]. One of the largest increases in Fos after removal of the litter was in the LHb.…”
Section: Fos Expression In Response To Anxiogenic Stimuli Is Modulatementioning
confidence: 94%
“…First, in five of them (mPOAd, mPOAv, LHb, SUM, VMH), and even in some sites that did not have significant main effects of or interactions with litter presence (e.g., CG, BSTd, MS, LSvl, PVNp, NAc, LH), a comparison of the unstimulated controls reveals that simply removing the litter produced a 2-6-fold increase in Fos expression. This is not the result of a physiological stress response, because temporary removal of the litter actually decreases maternal glucocorticoid levels, not increases them [24,78,90]. One of the largest increases in Fos after removal of the litter was in the LHb.…”
Section: Fos Expression In Response To Anxiogenic Stimuli Is Modulatementioning
confidence: 94%
“…In rats, Maeda et al (1989) showed that lactation-induced decreases in GnRH/LH secretion are rescued in 18-48 h after pup separation (PS) and are rapidly re-suppressed by subsequent re-exposure of pups. Li et al (1998) also reported the increase of plasma LH by 48-h PS and re-suppression by 24-h re-exposure of pups and Fukushima et al (2006) showed that estrogen responsiveness of LH secretion was restored within 6 h after PS. Although these studies suggest that the proximal cause of these rapid changes in GnRH/LH secretion is the suckling stimulus, the neuroendocrine mechanisms linking the modulation in suckling stimulus and the change in GnRH/LH secretion are not yet fully understood.…”
Section: Introductionmentioning
confidence: 94%
“…GnRH neurones can express Fos (43, 44) but, as in a previous investigation (21), glutamatergic stimulation of LH secretion was not associated with detectable Fos expression in GnRH perikarya. As proposed for rats (23), this lack of Fos expression may result from the threshold for NMA to stimulate GnRH cell function being lower than that necessary to induce detectable Fos expression in these cells.…”
Section: Discussionmentioning
confidence: 68%